Exercise interventions and serum IGF-1 levels in older adults with frailty and/or sarcopenia: a systematic review and meta analysis - Rui Chu; Mingming Li; Yeshou Xie; Yinuo Du; Tao Ni (Frontiers in Public Health)
ObjectiveInsulin-like growth factor-1 (IGF-1) is thought to play an important role in regulating skeletal muscle mass and function, with its decline potentially linked to age-related frailty and sarcopenia. Given the limitations of pharmacological and nutritional interventions, exercise may serve as a potential non-pharmacological strategy to modulate IGF-1 levels. The purpose of this study is to systematically evaluates the effects of exercise interventions on serum IGF-1 levels in older adults with frailty and/or sarcopenia using a meta-analysis approach.MethodsA systematic search was conducted in PubMed, Web of Science, Cochrane Library, EMBASE and Scopus (from inception to July 2025) to identify randomized controlled trials (RCTs) investigating the impact of exercise interventions on serum IGF-1 levels in older adults with frailty and/or sarcopenia. Data were analyzed using RevMan 5.4 and Stata 15.1, with standardized mean differences (SMD) and 95% confidence intervals (95% CI) calculated via a random-effects model. The protocol was registered with PROSPERO (CRD420251085472).ResultsA total of 11 studies (comprising 16 RCTs) were included, involving 604 participants (intervention group: 314; control group: 290), age range: 63.6 to 85.8 years old. Meta-analysis revealed that exercise interventions significantly increased serum IGF-1 levels in older adults with frailty and/or sarcopenia (SMD = 0.42, 95% CI: 0.23–0.60, p < 0.0001, I2 = 15%). Subgroup analysis demonstrated that combined training (aerobic + resistance) yielded the most pronounced effect (SMD = 0.60, 95% CI: 0.36–0.84, p < 0.00001, I2 = 0%), followed by resistance training alone (SMD = 0.35, 95% CI: 0.05–0.66, p = 0.02, I2 = 28%), whereas aerobic training alone showed no significant effect [SMD = 0.01, 95%CI: (−0.46, 0.48), p = 0.96, I2 = 0%]. Similarly, subgroup analysis revealed that exercise intervention could effectively improve serum IGF-1 levels in older adult individuals with frailty (SMD = 0.53, 95%CI: 0.07–0.98, I2 = 0%) or sarcopenia (SMD = 0.40, 95%CI: 0.19–0.61, I2 = 25%), with no statistically significant difference in effect sizes between the two groups.ConclusionExercise intervention can effectively increase serum IGF-1 concentrations in older adults with frailty and/or sarcopenia. The research results may provide key evidence-based basis for clinical non-pharmacological interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251085472.